A Leadership Typology for Professional Learning and Development - Christopher Bezzina; Mark A. Farrugia (IUL Research, 2022)
This reflective paper is inspired from a research by a school leader to promote teacher agency in professional learning and development. It draws on the similarities and differences of both leadership and facilitation roles to propose a typology that is shaped by roles and goals. We present here a critical view of a phenomenon that is often distinguished by styles and characteristics of leadership. Through the perspective shared here, we aim to contribute into the leadership discussions that specify and distinguish responsibilities. It complements with the axiom that leaders have a key role in concerting the vision and driving the goals of the organization.